Ethnobotany, phytochemistry and pharmacological significance of the genus Bulbine (Asphodelaceae). (5th October 2020) - Bodede, Olusola; Prinsloo, Gerhard
Abstract: Ethnopharmacological relevance: The genus Bulbine (Asphodelaceae) is spread across Southern Africa and Australia and has been traditionally used for various medicinal applications such as treating skin diseases, burns, diarrhoea, and sexually transmitted diseases. Aim of this review: The aim is to present a critical review of the ethnomedicinally important species of the genus Bulbine with a comprehensive overview of their chemical constituents and biological activities. Materials and methods: This paper is an overview of literature published on the genus Bulbine in the last six decades with regards to phytochemical composition and their respective pharmacological potentials with the aid of data obtained from the search engine Google Scholar with string searches performed using keywords to obtain relevant publications from scientific databases including ACS Journals, PubMed, Science Direct, SciELO, Sci Finder, Springer, Tailor & Francis, The Plant List Database, Web of Science and Wiley. Results: The literature survey reveals that only 12 species in the genus Bulbine have been reported to be used traditionally with scientific records of ethnomedicinal usage Anthraquinones appeared as the most abundant phytochemicals in the genus. Other isolated/detected metabolites include isofuranonaphthoquinones, flavonoids, and triterpenoids. Promising pharmacological activities have been reported by members of the genus with antiplasmodial, antitrypanosomal, antiviral, antioxidant, anticancer, anti-inflammatory and anti-microbial activity, potent wound healing properties as well as improved reproduction. Conclusions: This review showed the traditional uses of this genus and its preventative and curative properties in the management of the listed diseases providing support from bioassays of the tested compounds and extracts. State-of-the-art analytical techniques are required for the characterisation and quantification of the compounds within the genus. The efficacy of the therapeutic potential of the Bulbine species need to be further confirmed with pre-clinical and clinical studies. Graphical abstract: Image 1